Follicular dendritic cell sarcoma aggravated by hyaline-vascular Castleman's disease in association with paraneoplastic pemphigus: study of the tumor and successful treatment - Jing Wang; Xiaoyue Wang; Juan Xu; Pengfei Song (Sociedade Brasileira de Dermatologia, 2019)
Abstract The authors have successfully treated and monitored a case of paraneoplastic pemphigus in association with follicular dendritic cell sarcoma aggravated by hyaline-vascular Castleman's disease. The patient was a 56-year-old female who presented with recalcitrant erosive lichen planus of the oral cavity, tongue, and genital mucosa, along with polymorphous eruptions throughout her body. Histological examination of the cutaneous lesions, indirect immunofluorescence on rat bladder epithelium, and western blot of human keratinocyte proteins identified anti-epidermal antibodies in the patient's serum. Positron emission tomography and computed tomography scans found a mass in her retroperitoneal region. Pathology and immunohistochemistry investigation further corroborated the diagnosis of follicular dendritic cell sarcoma originated from hyaline-vascular Castleman's disease. Complete remission was achieved and the patient has been monitored for four years.